The effect of ligand, solvent and Cu(0) source on the efficient polymerization of polyether acrylates and methacrylates in aqueous and organic media1. Issue 32 (28th August 2015) - Simula, Alexandre; Nikolaou, Vasiliki; Alsubaie, Fehaid; Anastasaki, Athina; Haddleton, David M.
<x xml:space="preserve">Abstract</x> The synthesis of well-defined telechelic polyacrylates and polymethacrylates in organic and aqueous media via Cu(0)-mediated reversible-deactivation radical polymerization is thoroughly investigated.